A longitudial study of a neuropsychological rehabilitation program in Alzheimer's disease Estudo longitudinal de um programa de reabilitação neuropsicológica dirigido a pacientes com doença de Alzheimer - Jacqueline Abrisqueta-Gomez; Fabiola Canali; Vera L.D. Vieira; Ana Cristina P. Aguiar; Carmen S.C. Ponce; Sonia M. Brucki; Orlando F.A. Bueno (Arquivos de Neuro-Psiquiatria)
Our aim was to study the duration of benefits derived from a neuropsychological rehabilitation program (NRP) for dementia patients. METHOD: The participants in this study were three patients diagnosed as probable Alzheimer's disease in the initial-to-moderate phase; the three were taking anticholinesterases. They were submitted to a neuropsychological evaluation (NE) before the NRP and then revaluated after 12 and 24 months of treatment. The aim of our intervention was to do practical work with implicit and explicit residual memory by training them in everyday life activities, and using compensatory strategies and their intact cognitive abilities. RESULTS: Analysis of quantitative NE data (descriptive measures) after the first year of NRP showed cognitive improvement, functional stabilization and fewer behavioral problems. However, this improvement did not continue in the second year, and the disease maintained its characteristic progression. OBJETIVO: Estudar a duração do beneficio de um programa de reabilitação neuropsicológica (PRN) dirigido a pacientes demenciados. MÉTODO: Participaram deste estudo, três pacientes com diagnóstico de provável doença de Alzheimer em fase inicial a moderada. Todos faziam uso de anti-colinesterásicos e passaram por uma avaliação neuropsicológica (AN) antes de começar o PRN e reavaliação após 12 e 24 meses do tratamento. O alvo de nossa intervenção foi trabalhar de forma prática a memória explicita residual e implícita, através do treino das atividades da vida diária, uso de estratégias compensatórias e habilidades cognitivas ainda preservadas. RESULTADOS: A análise dos dados quantitativos (medidas descritivas) da AN mostrou, que após o primeiro ano do PRN houve uma melhora cognitiva, estabilização funcional e redução dos problemas comportamentais nos pacientes. No entanto, observamos que essa melhora não se estendeu para o segundo ano, mostrando a doença sua característica progressiva.